A simulation framework for cooperative intelligent transport systems testing and evaluation. (February 2019) - Aramrattana, Maytheewat; Larsson, Tony; Jansson, Jonas; Nåbo, Arne
Highlights: A framework consisting of driving-, traffic-, and network-simulators are proposed. Potential usages of the framework for testing and evaluation of C-ITS applications. Capability to study issues related to human drivers in the context of C-ITS. Abstract: Connected and automated driving in the context of cooperative intelligent transport systems (C-ITS) is an emerging area in transport systems research. Interaction and cooperation between actors in transport systems are now enabled by the connectivity by means of vehicle-to-vehicle and vehicle-to-infrastructure (V2X) communication. To ensure the goals of C-ITS, which are safer and more efficient transport systems, testing and evaluation are required before deployment of C-ITS applications. Therefore, this paper presents a simulation framework—consisting of driving-, traffic-, and network-simulators—for testing and evaluation of C-ITS applications. Examples of cooperative adaptive cruise control (CACC) applications are presented, and are used as test cases for the simulation framework as well as to elaborate on potential use cases of it. Challenges from combining the simulators into one framework, and limitations are reported and discussed. Finally, the paper concludes with future development directions, and applications of the simulation framework in testing and evaluation of C-ITS.